The Effectiveness of Integrating Learning Management to Online Project-Based Learning on Students' Metacognitive Abilities - Bambang Sigit Widodo; Sugeng Utaya; Muhamad Sholeh; Liknin Nugraheni (Indonesia Approach Education, 2023)
Metacognition is one of the important components to measure student learning achievement in the university. Metacognition knowledge can significantly measure students' critical thinking skills, especially in solving problems. The ability to solve problems serves as a bridge among metacognition as well as educational success. This study aims to determine metacognitive knowledge on the ability to solve complex problems in social geography. The sample of the research sample were 163 divided into two control and experimental groups. The experimental class used online project-based learning, and the control group used conventional learning. The instrument used to collect the metacognitive data uses was learning and Study Strategies Inventory (LASSI) adapted to the characteristics of students. By 77 items of LASSI were 48 items were valid and reliable used in this study. The result showed that the experimental group using online project-based learning had better metacognitive knowledge, especially on variables that had significant differences of p < 0.05, such as Information Processing, Attitude, Motivation, Self-Testing and Aids Studies. Furthermore, differences in the ability to solve complex problems of social geography are discussed in this study.